2017
DOI: 10.1002/wrna.1432
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and modern: hints of a core post‐transcriptional network driving chemotherapy resistance in ovarian cancer

Abstract: RNA‐binding proteins (RBPs) and noncoding (nc)RNAs (such as microRNAs, long ncRNAs, and others) cooperate within a post‐transcriptional network to regulate the expression of genes required for many aspects of cancer behavior including its sensitivity to chemotherapy. Here, using an RBP‐centric approach, we explore the current knowledge surrounding contributers to post‐transcriptional gene regulation (PTGR) in ovarian cancer and identify commonalities that hint at the existence of an evolutionarily conserved co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 135 publications
(234 reference statements)
0
11
0
Order By: Relevance
“…RBPs regulate the expressions of genes required for many aspects of cancer behaviors including its sensitivity to chemotherapy in post-transcriptional network ( 37 ). In the identified five RBPs, the expressions of CELF4, LRRFIP2, ZNF385A, and PPARGC1A were down-regulated, while the expression of NOP14 was up-regulated (all P < 0.001).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…RBPs regulate the expressions of genes required for many aspects of cancer behaviors including its sensitivity to chemotherapy in post-transcriptional network ( 37 ). In the identified five RBPs, the expressions of CELF4, LRRFIP2, ZNF385A, and PPARGC1A were down-regulated, while the expression of NOP14 was up-regulated (all P < 0.001).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Both MALAT1 and HOTAIR have been suggested as potential therapeutic targets to restore platinum sensitivity. The overexpression of PVT1 and HOTAIR were implicated in cisplatin resistance in cell line models by regulating apoptotic factors or activating the NF-κB (nuclear factor kappa B) pathway, respectively [ 75 , 76 ]. Intriguingly, increased levels of PVT1 after carboplatin-docetaxel treatment induced TP53 and TIMP1 (tissue inhibitor of metalloproteases-peptidase inhibitor 1) proteins expression concomitantly to decreased cell proliferation [ 77 ].…”
Section: Lncrnas and Their Association With Ovarian Cancermentioning
confidence: 99%
“…Prior studies showed that RBPs could regulate the functions of lncRNAs and coding genes through direct interactions with these RNA transcripts [31,32]. Thus, RBPs that had the probability to bind with RMRP and ZNRF3 mRNA were screened out through POSTAR database.…”
Section: Rmrp Regulated Znrf3 Expression and Mrna Stability Through Rmentioning
confidence: 99%
“…After 3 h of co-incubation, the optical density (OD) values were measured at 450 nm using the SpectraMax 190 microplate reader (Molecular Device, San Jose, CA, USA). For the measurement of cell survival rate, transfected cells (100µl/well) were seeded into 96-well plates for 24 h and then treated with different concentrations (8,16,32,64,128, or 256 µM) of TMZ for another 24 h. Next, 10µl of CCK-8 solution was added into each well. Three hours later, OD values were determined at 450 nm, followed by the determination of 50% inhibitory concentration (IC 50 ).…”
Section: Cck-8 Assaymentioning
confidence: 99%